Research and education in agrobusiness in Mosonmagyaróvár – the 200-year history - Hegyi, Judit (Applied Studies in Agribusiness and Commerce, 2020)
In 2018, the Faculty of Agricultural and Food Sciences of Széchenyi István University celebrated the bicentenary of its predecessor’s foundation. Agrobusiness courses played an important role in the university’s agricultural engineering program throughout this major time period. The aim of this study is to examine how the titles, the content, and the significance of the courses changed during the institution’s important periods. Institutional history publications and the academic textbooks of great professors provided the basis of this research. Business administration, accounting, and agricultural estimation studies courses were already dominant in the first curricula. Later, courses concerning business and agricultural economics gained more ground and were accompanied by other fields of study: agricultural statistics, agricultural politics, agricultural history, and agricultural economics. During this 200-year period, the education of economics and other social science courses was done within the departments of agricultural economics and marketing, work organization and factory management, and social science and business operations, with the contribution of internationally renowned professors: Pál Sporzon, Richárd Suschka, Árpád Hensch, Károly Világhy. The Hungarian Royal Economics Academy (1874-1942) can be considered as the first prime of the agricultural economics education. From the 1900s onwards, the courses became more specialized, their numbers continuously grew, the disciplines expanded, and the number of departments increased. The second prime is the first decade of the 2000s, when besides the traditional agricultural programs, the institution started teaching economic agricultural engineers in its undivided 5-year training. They were the most popular agricultural engineers in the labor market due to their well-balanced knowledge in agriculture and economics, as well as their excellent leadership skills. Having abandoned the economic agricultural engineering program, the institution currently educates, besides other agricultural majors, rural development agricultural engineers, whose skills the labor market does not know very well. The proportion of business related courses show a significant decline in the curriculum of traditional agricultural programs as well. JEL code: N30